Whither Winter: The Altered Role of Winter for Freshwaters as the Climate Changes. Issue 6 (1st June 2022) - Cotner, James B.; Powers, Stephen M.; Sadro, Steven; McKnight, Diane
Abstract: Our changing climate is having effects on freshwater ecosystems in all seasons, especially winter. High latitude lakes, wetlands, and rivers are experiencing shorter periods of ice cover, and lower latitudes systems that used to freeze are experiencing open water conditions throughout the winter. A 2019 AGU Chapman conference convened aquatic scientists to examine these changes and address the implications of changing winters to aquatic life, chemistry, and physics. Several studies demonstrate decreased ice cover duration than in the past. The removal of an ice "lid" from lakes and rivers impacts the exchange of gases with the atmosphere and the predominant types of metabolism occurring in the waters below, with the potential for more photosynthesis and an increase in oxic versus anoxic metabolism when the lid is removed. Multiple studies indicated an increase in the interannual variability of winters, especially in terms of ice‐cover duration and ice quality. Increased variability may simply be an outcome of a more variable winter climate or small differences in environmental conditions such as temperature that can have strong effects on gas exchange, light transmission, and turbulence when ice forms. A question that merits further consideration is whether and how winters of shorter duration and severity will change the dynamics of freshwater systems. Are there memory or legacy effects that carry over to the next season or year? There is much work to be done to understand how changing winters will impact the biogeochemical behavior of lakes and rivers in the coming decades. Plain Language Summary: Winters at mid‐high latitudes are changing rapidly with important implications for freshwater ecosystems. An AGU Chapman conference, convened in 2019, brought together scientists to outline what we know about the changes that are occurring and what questions need further study. This special issue is a collection of the papers that developed from that workshop. These studies demonstrate that lakes and rivers at mid‐high latitudes are experiencing less ice cover duration and greater variability in year‐to‐year ice cover. Changing ice and snow cover impacts processes occurring under ice in winter by altering the light regime, mixing, biota present, and the availability of oxygen. There are many important research questions regarding winter dynamics that still need to be addressed but one of the most important ones has to do with how changing winters might influence the biota in other seasons. Key Points: Several of the papers point to interannual variability in winter and seasonal ice cover along with decreased ice cover duration Available winter datasets have grown supporting conceptual developments, but increased efforts focused on ecological responses are needed Future research should examine connections between seasons, deploy submersed sensors year‐round, and use remote sensing approaches